Identifikasi Status Gizi pada Remaja di Pesantren Al-Hidayah - Chandra, Filius; Jeki, Andika Gustra; Fatmawati, Tina Yuli (Prosiding Seminar Kesehatan Nasional, 2024)
Nutritional problems remain a significant challenge in global health, particularly among teenagers. Common issues include malnutrition and overnutrition. If not addressed properly, these conditions can negatively impact adolescent health in the future. According to Riskesdas data, the prevalence of nutritional status (BMI-for-age) among adolescents aged 16–18 years in Indonesia shows 1.4% are very thin, 6.7% are thin, 9.5% are overweight, and 4% are obese. In Jambi Province, 1.5% of teenagers are very thin, 6.5% are thin, 7.8% are overweight, and 2.7% are obese. The aim of this research is to assess the nutritional status of adolescents at the Al-Hidayah Islamic Boarding School in Jambi City. This study is descriptive research designed to provide an overview of the variables studied. The population consists of 451 adolescents at the boarding school, with a sample size of 90 participants. The research instruments included a questionnaire and measurements of nutritional status using scales and microtools. The data were analyzed univariately to determine the frequency distribution of the variables studied. The results showed that the majority of respondents were female (52.2%), with most aged 16 years (38.9%). Regarding nutritional status, the majority of respondents had normal nutritional status (64.4%, or 58 participants). It is recommended that teenagers consume balanced nutrition to support growth, maintain health, and enhance productivity in the future